2011
DOI: 10.1080/09638190903045557
|View full text |Cite
|
Sign up to set email alerts
|

New exports matter: Discoveries, foreign direct investment and growth, an empirical assessment for Middle East and North African countries

Abstract: Export diversification has become a priority goal for the development of the Middle East and North African (MENA) countries. In this article, we aim at measuring both the effects of exports' diversification on growth in MENA countries and the way new exports and foreign direct investment (FDI) interact with each others in the process of growth. Although the effects of FDI on growth have been scrutinized by numerous studies up to now, the effects of diversification and discoveries in export have only very recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Nicet-Chenaf and Rougier (2011) examined the effect of exports diversification on economic growth as well as the ways foreign direct investment and exports interact with each other in the MENA countries. They found that export diversification and FDI increases economic growth, while imports are the source of technological spillover in the developing countries and facilitates global integration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nicet-Chenaf and Rougier (2011) examined the effect of exports diversification on economic growth as well as the ways foreign direct investment and exports interact with each other in the MENA countries. They found that export diversification and FDI increases economic growth, while imports are the source of technological spillover in the developing countries and facilitates global integration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Source: UN-COMTRADE and authors' calculations. (Amighini abd Sanfilippo, 2014;Nicet-chenaf and Rougier, 2011). Compared to its peers, Mauritania has attracted a significant amount of FDI over the past decade (Figure 28), but extractive industries were the main destination of these inflows (Figure 29).…”
Section: Mauritania Has Struggled To Diversify Exports Away From Extractivesmentioning
confidence: 99%